Models for bonding in chemistry - Magnasco, Valerio (Wiley, 2010)
This title presents the essentials of the different bonds occurring in chemistry. The book presents the essential elements of the variation approach to either total or second-order molecular energies, introduces a model of bonding in homonuclear and heteronuclear diatomics, and much more